Gene copy number alteration profile and its clinical correlation in B-cell acute lymphoblastic leukemia. Issue 2 (1st February 2017) - Gupta, Sanjeev Kumar; Bakhshi, Sameer; Kumar, Lalit; Kamal, Vineet Kumar; Kumar, Rajive
Abstract: The genes related to B-cell development are frequently altered in B-cell acute lymphoblastic leukemia (B-ALL). One hundred sixty-two newly diagnosed B-ALL cases, median age 8.5 years (2 months–67 years), were prospectively analyzed for copy number alterations (CNAs) in CDKN2A/B, IKZF1, PAX5, RB1, ETV6, BTG1, EBF1, and pseudoautosomal region genes ( CRLF2, CSF2RA, IL3RA ) using multiplex ligation-dependent probe amplification. The CNAs were detected in 114 (70.4%) cases; most commonly affected genes being CDKN2A/B- 55 (34%), PAX5- 51 (31.5%), and IKZF1- 43 (26.5%). IKZF1 and RB1 deletions correlated with higher induction failure. Patients classified as good-risk, according to the integrated CNA profile and cytogenetic criteria, had lower induction failure [5 (8.6%) vs. 20 (25.3%); p = 0.012]. Those classified as good-risk, based on CNA profile irrespective of cytogenetics, also showed lower induction failure [6 (9.4%) vs. 19 (26%); p = 0.012]. The CNA profile identified patients with better induction outcome and has a potential role in better risk stratification of B-ALL.